A Call for Enhanced Training and Action on the Intersections of Mental Health, Decent Work, and Career in Counselling and Psychotherapy - Hudson Breen, Rebecca E.; Lawrence, Breanna (Canadian Journal of Counselling and Psychotherapy, 2021)
Although career is identified as a key element of counselling and counselling psychology, currently many students and professionals within these disciplines do not identify career as integral to their practice. This neglect persists despite ongoing calls for increased awareness of career development issues from scholars in the field. The authors argue that the integration of the psychology of work and career is essential to ethical practice in counselling and counselling psychology as well as a necessary area of competency in acting on fostering social justice and decent work as a human right. Recommendations for integrating career within counsellor education and counselling psychology training programs are discussed.